1962
DOI: 10.1172/jci104658
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vaginal Smear, Serum Gonadotropin, Protein-Bound Iodine, and Thyroxine-Binding as Measures of Placental Adequacy*

Abstract: During pregnancy the characteristic increase in the thyroxine-binding capacity of the circulating globulin, TBG (1-3), is associated with a retarded rate of thyroxine turnover (4) and an increase in the concentration of hormonal iodine (PBI) in the plasma (1-4). These alterations in iodine metabolism have not been found in women with choriocarcinomas who excrete large quantities of chorionic gonadotropin (5), but do occur in nonpregnant individuals given large quantities of estrogens (6-8). It has been conclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1964
1964
1986
1986

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 38 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…This is well illustrated in the euthyroid pregnant subjects with the characteristic elevation of PBI attributable to increased TBG concentration (1,(17)(18)(19)(20)(21)(22)(23)(24), but a low per cent free thyroxine, giving a computed free thyroxine iodine concentration in the low normal range. It is considered likely that the physiological activity of thyroxine depends upon the concentration of unbound hormone.…”
Section: Methodsmentioning
confidence: 74%
“…This is well illustrated in the euthyroid pregnant subjects with the characteristic elevation of PBI attributable to increased TBG concentration (1,(17)(18)(19)(20)(21)(22)(23)(24), but a low per cent free thyroxine, giving a computed free thyroxine iodine concentration in the low normal range. It is considered likely that the physiological activity of thyroxine depends upon the concentration of unbound hormone.…”
Section: Methodsmentioning
confidence: 74%
“…In an earlier paper we emphasized that a link exists between low globulin-bound iodine (the equivalent of the present TBG-held fraction), and the incidence of habitual abortion (Winikoff et al, 1960). Similarly Nicoloff et al (1962) found the TBG assay most valuable in predicting the outcome of pregnancy. Other authors maintain that a failure of thyroxine and/or TBG to rise from pregestational levels (no matter what they were) does not augur well for the outcome of pregnancy.…”
Section: Discussionmentioning
confidence: 91%
“…THERE have been many attempts to correlate an unsuccessful outcome of pregnancy with Five groups of patients were investigated: inadequate thyroid function (Man et al, 1951 ; Group 1.-70 normal pregnant women (con-Dowling et al, 1956;Winikoff et al, 1960; trols), Nicoloff et al, 1962 and1970;Magnin et al, Group 2.-36 pregnant women who carried a 1968; Jones and Man, 1969). A high proportion pregnancy to term but had a past of women with a low blood thyroxine level have history of two or more spontaneous either a premature delivery or a sFontaneous abortions, abortion (Jones and Man, 1969 were free from overt thyroid disease.…”
Section: Malvina Malinek Research Biochemist Ewen Downie Metabolic Umentioning
confidence: 99%
“…Generally, it has been claimed that inade quate thyroid function is combined with un successful outcome of pregnancy [1][2][3][4], Also, there exists a link between globulin-bound iodine (GBI) and the outcome of pregnancy, since low GBI has been claimed to be a warn ing of threatening abortion [3], Later on it has been reported that TBG is the most valuable variable as a predictor for the outcome of pregnancy and even so when compared to serum HCG in reflecting placental function [4], In that study an indirect method was used for estimating TBG. In the present study we used a direct method of measuring TBG.…”
Section: Discussionmentioning
confidence: 99%